Sustained Maternal Smoking Triggers Endothelial-Mediated Oxidative Stress in the Umbilical Cord Vessels, Resulting in Vascular Dysfunction - Szabolcs Zahorán; Péter R. Szántó; Nikolett Bódi; Mária Bagyánszki; József Maléth; Péter Hegyi; Tamás Sári; Edit Hermesz (MDPI AG, 2021)
Nitric oxide (NO) bioavailability is fundamental in the regulation of redox balance and functionality of the endothelium, especially in the case of the umbilical cord (UC), which has no innervation. The analysis of UC vessel-related complications could serve as a useful tool in the understanding of the pathophysiological mechanisms leading to neonatal cardiovascular disorders. Therefore, the aim of this study was to characterize the mechanisms that rule the severity of prenatal endothelial dysfunction, induced by the long-term effect of maternal smoking. Our analysis describes the initiation and the consequences of endothelial nitric oxide synthase (NOS3) deactivation, along with the up-regulation of possible compensatory pathways, using structural, molecular and biochemical approaches. This study was carried out on both the UC arteries and veins originated from neonates born to non-smoking and heavy-smoking mothers. The alterations stimulated by maternal smoking are vessel-specific and proportional to the level of exposure to harmful materials passed through the placenta. Typically, in the primarily exposed veins, an increased formation of reactive oxygen species and an up-regulation of the highly-efficient NOS2-NO producing pathway were detected. Despite all the extensive structural and functional damages, the ex vivo heat and cadmium ion-treated UC vein pieces still support the potential for stress response.